Effect of family nursing care training for puskesmas nurses on increasing family independence in the health sector - Ani Susiani; Amelia Wati (Science Midwifery, 2023)
Family nursing care as a form of community health activities is also proven to be able to increase family independence in dealing with health problems that they experience independently. However, in practice the documentation of family nursing care as physical evidence of the implementation of the family nursing care process carried out by puskesmas nurses still does not meet the standards, so this study aims to determine the effect of family nursing care training for puskesmas nurses on increasing family independence in the health sector. in the work area of ​​the Indramayu Regency Health Office in 2022. The results of this study indicate that training can increase the average value of knowledge regarding family nursing care and documentation carried out by puskesmas nurses from 12, 44 and increased to 19.76. This increase in knowledge then has an influence on increasing the ability of nurses to carry out family nursing care. This is evidenced by the increasing independence of the community in the health sectornamely the number of KM IV increased by 48.6% when compared to before the training, which was 35.0%.Thus that the community and puskemas can benefit from knowing the impact of family nursing care training on puskesmas nurses on boosting family independence in the healthcare sector.